KOMUNIKASI PEMIMPIN DALAM STRATEGI POSITIONING GUNA MENINGKATKAN DAYA SAING PERGURUAN TINGGI ISLAM - SITI AMINAH (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2018)
One of efford to increase competition islamic university (PTI) is an ability to do differentation strategy by positioning or a distinctive placement in the public eye. Positioning PTI as an organization in the minds of stakeholder is very important so the organization can success in winning the competition. PTI must be keen to position its service products as something unique and valuale so that the product/organizations can get a place in the mind of stake holders. Facing a very thought challange in th future, PTI is necessar to prepare leaders by having various roles: a) As planner, b) As managers, c) As supervisiors and evaluatior, d) As communicator by using good communication PTI leaders can make their staff highly commited to improve the quality of education. The leader of PTI should always build effective communication with its members encourage one to work as the leader wants to achieve the organization goals. Verbal communication from a leader of PTI in positioning strategy to increase PTI competition is by using positioningsentenc have invaluable meaning in giving focus and purity a formation or strategi building and marketing tactics. Non verbal communication form from a PTI leaders is by giving the best service PTI leaders is as a khadimul ummah( servant of the people). It means that they have to give the best service to the costumer either internal customer or external the best leader is a leader who are able to give the best way to lead that to communicate in the best way to their members and institution costumer.